Pengaruh Apoteker Pengelola Apotek (APA) Terhadap Kualitas Pelayanan Kefarmasian Di Apotek Kabupaten Bangkalan - M. Shofwan Haris (DIA: Jurnal Administrasi Publik, 2014)
Nowadays, the paradigm of pharmacy services has began into patient orientation and known as Pharmaceutical Care. The role of pharmacist is giving a consultation, information, and education related with medical therapy to patient, directing patient to do healthy lifestyle therefore it will supporting the medical process. Besides, it could monitor the medical theraphy’s result by the patient and also collaborate with other healthy proffesional to improve quality life of the patient. The objective of this research is to explore APA’s factor that affects the quality pharmacy services of pharmacies which has not been done at Bangkalan District by the pharmacist that the manager of the pharmacy (APA) and to determine the variables of APA’s factor the most influence on quality pharmacy services of pharmacies. This research used an observational framework of cross-sectional analytic and sample collecting methode by Simple Random Sampling towards 52 pharmacies at Bangkalan District. Type of data has been used was primary data based on give questioner and observation towards APA at Bangkalan District. The results using multiple linear regression. The results showed that the partial all of  APA’s factor that tangible, reliability, responsiveness, assurance, and emphaty had a significant impact on quality pharmacy service of pharmacies with level of significance under of α = 0,05. While simultaneously the APA’s factor significant influence on quality pharmacy service of pharmacies at Bangkalan District.Keywords: the Manager of the Pharmacy (APA), quality pharmacy service of pharmacies